Analysis fear of negative evaluation (FNE) level in physical education based on gender and age - Syamsuddin, Irfan Fadhil; Sutresna, Nina (Universitas Suryakancana, 2024)
In physical education, many aspects must be considered so that it can see whether the physical education learning provided can provide good results, in physical education it is very important to evaluate students so that teachers can provide direction for effective learning, this must be reviewed with the level of fear of negative evaluation in students so that teachers can adjust what will be given to students. This study aims to determine the level of fear of negative evaluation in physical education based on gender and age. The research method used is descriptive quantitative method using survey research design by distributing questionnaires through Google Form which is done directly. The population in this study were grade XI students in 3 high schools with a total of 610 students. The researcher's sampling technique used Purposive Sampling technique by including grade XI students, students aged 16-17 years. The instrument used in this study is the Brief Fear of Negative Evaluation Scale from Leary (1983). All data collected from the research sample were tested for assumptions, namely normality and homogeneity, after declaring the data to be normally distributed and homogeneous, then the analysis was carried out using the mean difference test (Independent T-Test). The results of the analysis show that the level of FNE of male and female students is significantly different (p_value 0.00 < 0.05), and also based on age, there is a significant difference (p_value 0.03 < 0.05). Based on the results of the analysis, it can be concluded that the level of FNE in physical education based on gender and age has different FNE. Important implications of the results of this study, considering the category of gender and age differences should be distinguished as one of the psychological parameters both in the form of assistance and intervention can be given to students in physical education so that learning takes place effectively.